The Bezold-Jarisch Reflex and The Inflammatory Response Modulation in Unanesthetized Endotoxemic Rats - Brognara, Fernanda; Castania, Jaci Airton; Ribeiro, Aline Barbosa; Santos-Júnior, Nilton Nascimento; Salgado, Helio Cesar (Frontiers in Physiology, 2021)
Evidence indicates that the activation of the parasympathetic branch of the autonomic nervous system may be effective in treating inflammatory diseases. Previously, we have described that the baroreflex activation displays anti-inflammatory properties. Analogous to the baroreflex, the Bezold-Jarisch reflex also promotes parasympathetic activation with simultaneous inhibition of the sympathetic system. Thus, the present study aimed to evaluate whether the Bezold-Jarisch reflex activation would also have the ability to reduce inflammation in unanesthetized rats. We used lipopolysaccharide (LPS) injection (5 mg/kg, i.p.) to induce systemic inflammation in male Wistar Hannover rats and phenylbiguanide (PBG) administration (5 μg/kg, i.v.) to activate the Bezold-Jarisch reflex. The spleen, heart, hypothalamus, and blood sample were collected to determine the levels of cytokines. As compared to baseline, PBG reduced the arterial pressure (115 ± 2 vs. 88 ± 5 mmHg) and heart rate (380 ± 7 vs. 114 ± 26 bpm), immediately after its administration, confirming the activation of the parasympathetic and inhibition of the sympathetic system. From the immunological point of view, the Bezold-Jarisch reflex activation decreased the plasma levels of TNF (LPS: 775 ± 209 vs. PBG+LPS: 302 ± 60 pg/mL) and IL-6 levels in the spleen (LPS: 37 ± 6 vs. PBG+LPS: 24 ± 4 pg/mg of tissue). However, it did not change the other cytokines in the plasma or the other tissues evaluated. These findings confirm that the Bezold-Jarisch reflex activation can modulate the inflammation and support the sense that the cardiovascular reflexes regulate the immune system.